Drug‐Induced Cauda Equina Syndrome in an 8‐Year‐Old Boy With Acute Lymphoblastic Leukemia: An Uncommon Case Report - Marzieh Babaee; Mohsen Javadzadeh; Ali Hazeghi (Clinical Case Reports)
ABSTRACT Intrathecal methotrexate can cause cauda equina syndrome in pediatric ALL patients, as demonstrated in this rare case of an 8‐year‐old boy. Symptoms included progressive limb weakness and urinary retention. Early recognition, prompt discontinuation of the offending agent, and multidisciplinary management are crucial. Vigilant neurological monitoring is essential for pediatric acute lymphoblastic leukemia patients receiving intrathecal chemotherapy.